Factores asociados al vacío quirúrgico en pacientes con fractura de cadera en el Hospital Regional Docente de Trujillo - Sanchez Buitrón, Susan Katherine (2019)
Objective: To identify factors associated with surgical delay in patients with hip fracture attended in Hospital Regional Docente de Trujillo. Materials and methods: Observational, descriptive, cross-sectional study. 64 clinical histories of patients hospitalized for hip fracture at the Orthopedics and Traumatology Unit of HRDT between November 1, 2018 and June 30, 2019 were analyzed. Results: The surgical delay was 0-4 days in 7, 81% (95% CI: 2.58-17.30), 5-9 days in 57.81% (95% CI: 44.93-70.69) and> 9 days in 34.38% (95% CI: 21-96-46.79). 21 male and 43 female patients. 59 patients had SIS and 5 did not. 24 patients had 0-1 comorbidities, 36 of 2-3 comorbidities and 4 had> 3 comorbidities. 6 patients received antithrombotic treatment before admission and 58 not. 62 patients had INR <1.5 and 2 had INR ≥1.5. 50 patients had fracture type 31-A and 14 type 31-B. When applying chi-square with a 5% level of significance, there is only an association between surgical delay and SIS. Conclusion: Having a comprehensive health insurance is significantly associated with more prolonged surgical delay in patients with hip fracture.